Children at transition from primary school reflecting on what schools are for – narratives of connectedness, (mis)recognition and becoming - Gilligan, Robert; Scholtz, Jennifer (My University, 2021)
This article draws on a school-based case study carried out in Scotland with 11–12-year-olds reflecting on their views and experiences of school before transitioning from primary to secondary school. Drawing on Honneth’s recognition theory, and the dimensions of love, rights and solidarity, the findings show that school was seen by children as a place of dialogue, reciprocity and recognition; the learning and knowledge activities cannot be separated from the relational and emotional aspects. When misrecognition happens, subjects’ identity and sense of self-respect can be deeply violated.
PUBLISHED
Keywords: School transitions; School community; Recognition theory; Primary to secondary school transition; Meaning of school; Children’s rights; Children’s perspective; Children’s friendships; Becoming; Belonging; Inclusive Society